The Role of Labor Unions in Negotiating Compensation and Remuneration Toward Employee Performance at PT Dima Beverages International, Subang Branch, West Java - Farida, Syarifah Ida; Zulkarnain, Iskandar; Agustari H, Tiara (Jurnal Multidisiplin Sahombu, 2025)
This study explores the strategic role of labor unions in negotiating compensation and remuneration and their influence on employee performance at PT Dima Beverages International, Subang Branch, West Java. Employing a qualitative descriptive method, data were collected through semi-structured interviews, observations, and document analysis. The findings reveal that labor unions play a pivotal role not only in advocating for fair compensation but also in enhancing communication, transparency, and workplace motivation. Unions act as strategic partners, bridging employee aspirations and management decisions, contributing to policy development and fostering employee well-being. The research highlights that active union involvement correlates with improved performance, reduced absenteeism, and higher loyalty. Negotiations supported by data and mutual respect lead to more equitable outcomes. Despite limited negotiation capacity and access to information, unions contribute significantly to industrial harmony. This study provides practical insights for strengthening union roles in private sector labor relations, especially in labor-intensive industries in Indonesia.